GENETIC VARIABILITY FOR GRAIN QUALITY TRAITS IN AROMATIC RICE (Oryza sativa L) (Bangladesh Journal of Plant Breeding and Genetics, 2011)
Forty five aromatic rice genotypes were evaluated to assess the genetic variability and diversity on the basis of nine characters. Significant variations were observed among the genotypes for all the characters (grain breadth (mm), grain length (mm), grain L/B ratio, gelatinization temperature (score), gel consistency (mm), amylose content (%), protein content (%), 1000 grain weight (g) and grain yield per plant (g)) studied. High GCV, PCV, heritability and GA as observed in amylose content, grain length average and L/B ratio suggested that these three characters could be transmitted to the progeny. Multivariate analysis revealed that 45 genotypes were grouped into six clusters. There were marked variations in intra-cluster distances, which ranged from 0.482 to 7.851. The highest intra cluster mean for five traits (amylose content, width average, L/B ratio, length average, 1000 grain weight) was obtained from cluster I constituted 10 genotypes. Thousand grain weight and amylose content have been found to contribute maximum towards genetic diversity in 45 genotypes of aromatic rice.DOI: http://dx.doi.org/10.3329/bjpbg.v24i2.17002